2018
DOI: 10.3322/caac.21452
|View full text |Cite
|
Sign up to set email alerts
|

Timely follow‐up of positive cancer screening results: A systematic review and recommendations from the PROSPR Consortium

Abstract: Timely follow-up for positive cancer screening results remains suboptimal, and the evidence base to inform decisions on optimizing the timeliness of diagnostic testing is unclear. This systematic review evaluated published studies regarding time to follow-up after a positive screening for breast, cervical, colorectal, and lung cancers. The quality of available evidence was very low or low across cancers, with potential attenuated or reversed associations from confounding by indication in most studies. Overall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 128 publications
0
86
1
Order By: Relevance
“…In the past 50 years, the incidence and mortality of lung cancer has been reported to have increased significantly, accounting for the first in all malignant tumors, especially in men . Currently, researchers have spared no efforts to explore the pathogenesis of lung cancer in order to apply it to clinical treatment as soon as possible . However, effective interventions and procedures for NSCLC have so far been rare.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 50 years, the incidence and mortality of lung cancer has been reported to have increased significantly, accounting for the first in all malignant tumors, especially in men . Currently, researchers have spared no efforts to explore the pathogenesis of lung cancer in order to apply it to clinical treatment as soon as possible . However, effective interventions and procedures for NSCLC have so far been rare.…”
Section: Introductionmentioning
confidence: 99%
“…The epithelial-mesenchymal transition (EMT) is characterized by the loss of cell polarity and cell-cell adhesion in epithelial cells accompanied by the acquisition of migratory and invasive properties and the transition to mesenchymal stem cells [4,13,14]. EMT is essential for numerous developmental processes and human diseases including wound healing, organ fibrosis and the initiation or the metastasis in cancer progression [15][16][17]. Recent researches have revealed that EMT plays a critical role in the progression of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have spared no efforts to determine the mechanism of lung cancer and to accelerate the clinical treatment. 5,6 However, to date, there are few interventions and operations that are effective for lung cancer. 7 Therefore, it is very important to explore new prognostic markers and drug targets for lung cancer.…”
Section: Introductionmentioning
confidence: 99%